Stress-dependent method for calculating the modulus improvement factor in geocell-reinforced soil layers. Issue 1 (February 2021) - Garcia, R.S.; Avesani Neto, J.O.
Abstract: This paper presents an analytical method for determining the modulus improvement factor (MIF) in geocell-reinforced soil layers. Using a modified version of the hyperbolic soil model as a constitutive model, the method is developed based on the soil-reinforcement interaction relating nonlinear elastic soil behavior to the linear elastic response of the reinforcement. The proposed method, in an original way, explicitly takes into account the geometry of the geocell pocket, effects of soil and geocell-reinforcement stiffness, compaction-induced stresses, soil strength and strain compatibility. The method can be used both analytically and using simple and presented non-dimensional charts. Parametric analyses show that the reinforcement, soil relation and the stresses induced during the compaction procedure are the major factors influencing MIF. An evaluation using data from several laboratory, full-scale and field experiments in works is presented showing good predictive capability of proposed method. An application procedure for calculating MIF is presented. Highlights: Analytical method for determining the modulus improvement factor (MIF) in geocell-reinforced soil layers. Explicitly takes into account geometry, soil and geocell stiffness, compaction-induced stresses, and strain compatibility. Simple and easy to apply, especially when using non-dimensional charts. Good predictive capability even in full-scale experiments and instrumented works.